(untitled) (Bangladesh Journal of Infectious Diseases, 2023)
Background: Vaccination is now considered the most effective measure to prevent the harm resulting from the SARS-CoV-2. Mass vaccination has been started in different regions of the world, including Bangladesh. Objective: The present work has been done to discover the Bangladeshi people’s attitude, perception towards COVID-19 vaccines, and their willingness to be vaccinated. Methodology: This cross-sectional analysis was performed from the online survey data collected from 01 August 2021 to 17 august 2021 from Bangladeshi people over 21 years old at the Department of Pharmacy, Northern University Bangladesh. Results: Among the total participants (517), the majority (60.74%) gave a positive response for being vaccinated. The reasons for unwillingness to be vaccinated were listed as adverse effects of the vaccine (46.04%), complex procedures of vaccination (18.32%), doubtfulness about the vaccine’s efficacy (15.35%), reduced risk perception about COVID-19 (15.35%) and needle phobia (4.95%). Conclusion: It is revealed from the current study that education and media can motivate a person’s attitude towards vaccination. To bring mass people under the vaccination program, it is necessary to broadcast proper and authentic information about vaccines. Besides, the procedure of getting vaccines should be simpler. Bangladesh Journal of Infectious Diseases, December 2023;10(2):65-70